ANALISIS KESALAHAN HASIL TERJEMAHAN MAHASISWA SASTRA INGGRIS UNHAS DALAM MENERJEMAHKAN NASKAH BAHASA INDONESIA KE DALAM BAHASA INGGRIS - Saleh, Noer Jihad (JURNAL ILMU BUDAYA, 2014)
This study aimed to describe the error analysis of Indonesian - English made by the student of English Departmentof Unhas . This research is descriptive qualitative .The data collection by means of quistionaire distributionquestionnaires , and the provision of translation tasks t made by the respondents . The subjects of this is students ofEnglish Department Unhas , while its object is tranted texts made by the students. Data analysis performed „content analysis approach‟ concerning with grammatical errors and lexical errors . The results of the study indicatethat translating Indonesian - English exts more difficult, compared to English - Indonesian taranslation. Thisrelates to the level of English competence of the translator .In addition based on the analysis of the results oftranslation errors of students , the total number of lexical errors is little more compared to grammatical errors . Thegrammatical errors, include: structure , coherence and morphological aspects . While errors at lexical aspectsinclude terminology , expressions , and cultural content . The study also found that the tendency of studentsintranslating the Source language text, neglecting the the proper translation process, but they translate the textsdirectly from the source language into thetarget language .Keywors: translation, error analysis, lexical, grammaticalthe